2014
DOI: 10.1016/j.bbalip.2013.11.011
|View full text |Cite
|
Sign up to set email alerts
|

cis-Prenyltransferase AtCPT6 produces a family of very short-chain polyisoprenoids in planta

Abstract: cis-Prenyltransferases (CPTs) comprise numerous enzymes synthesizing isoprenoid hydrocarbon skeleton with isoprenoid units in the cis (Z) configuration. The chain-length specificity of a particular plant CPT is in most cases unknown despite thecomposition of the accumulated isoprenoids in the tissue of interest being well established. In this report AtCPT6, one of the nine Arabidopsis thaliana CPTs, is shown to catalyze the synthesis of a family of very short-chain polyisoprenoid alcohols of six, seven, and ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 43 publications
1
36
0
1
Order By: Relevance
“…AtCPT1 and AtCPT6 are expressed exclusively in root tissue, localize to the endomembrane system, and synthesize long-chain (C95-110) and short-chain (C35) polyprenols, respectively (Cunillera et al, 2000;Oh et al, 2000;Kera et al, 2012;Surmacz et al, 2014). The physiological function(s) of these polyprenols are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…AtCPT1 and AtCPT6 are expressed exclusively in root tissue, localize to the endomembrane system, and synthesize long-chain (C95-110) and short-chain (C35) polyprenols, respectively (Cunillera et al, 2000;Oh et al, 2000;Kera et al, 2012;Surmacz et al, 2014). The physiological function(s) of these polyprenols are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…N-Glycans are crucial for plant growth under stress conditions (Strasser, 2016); therefore, reprogramming of the Dol-14 to Dol-17 biosynthetic route could be indispensable for plant homeostasis. Long-and short-chain Dols are possibly not involved in protein glycosylation (Schenk et al, 2001;Surmacz et al, 2014) but instead could act as a shield against ROS or fulfill other as yet unknown functions.…”
Section: Discussionmentioning
confidence: 99%
“…The changing ratio of Dol families and the contrasting responses of different CPT genes in response to osmotic stress suggested that at least three CPTs take part in Dol biosynthesis. Since CPT6 produces shorter prenyl alcohols (Kera et al, 2012;Surmacz et al, 2014), CPT3 and/or CPT7 might operate to synthesize dominating Dols. Moreover, out of six CPTs expressed in Arabidopsis roots, CPT3 seems the most similar to the yeast Rer2 CPT, synthesizing a family of Dols with Dol-16 dominating ( Fig.…”
Section: Dol Metabolism Upon Osmotic Stress: Biochemical Analysismentioning
confidence: 99%
“…Z,E-DecPP from M. tuberculosis was the first described cis-PT utilizing a different allylic substrate other than FPP (17,31). In Arabidopsis thaliana, AtCPT6 functions in response to abiotic stress (32,33); however, the AtCPT6 product most likely does not serve as lipid carrier in glycosylation reactions.…”
Section: Classification Of Cis-ptsmentioning
confidence: 99%